An Application of Inversion Technique to 1-Dimensional Gravity Data in Bayesian Framework using Monte Carlo, Metropolis, and Simulated Annealing Algorithm - Adam Sukma Putra; Wahyu Srigutomo; Yuant Tiandho; Herlin Tarigan; Yanti Yanti (Institut Teknologi Bandung, 2019)
The purpose of this paper is to present a simulation to the inversion methods applied to geophysical exploration. Anapplication of Monte-Carlo, Metropolis, and Simulated Annealing techniques to 1-Dimensional gravity inversion inBayesian framework has been studied. Differences between these methods are observed in both single parameterinversion and simultaneous multi parameter inversion. After selecting the best inversion strategy from the three methods,a further investigation was investigated. Multi parameter inversion for two anomalies is simultaneously carried out andresults are observed. The synthetical data of GRAV2DC free source were used instead of observed data.